ANALISIS CITRA NEREK, POSITIONING PRODUK DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BAJU THE EXECUTIVE DI SOLO PARAGON MALL - Fitrysia Hanggraini; Ida Aryati; Rochmi Widayanti (ITB AAS INDONESIA Surakarta, 2019)
The goal of this study is the quality of brand image, positioning product, products, and lifestyle locations for clothing store the executive di solo paragon mall. The population in this study were consumers who bought products from The Executive at Solo Paragon Mall. The sampling technique uses accidental sampling, ie sampling is done by giving a questionnaire to get a sample based on the users of the product from The Executive who were met at the time of the research, which was taken from the research area. The data analysis method used in this study is descriptive statistics all analysis and regression analysis. Descriptive statistics of all analyzes, all interpretations, data obtained, and results of data processing carried out, carried out with explanations, explanations, and explanations. Regression analysis includes validity and reliability testing, classic assumption test, multiple regression analysis, determination test, t test, and l test. The results of the F test show that brand image, product positioning, and lifestyle have a simultaneous effect on purchasing decisions at the executive clothing store at the paragon mall solo. Brand image has a positive effect on purchasing decisions at the executive clothing store at Paragon Mall. Positioning products have a positive effect on purchasing decisions at the executive clothing store in Paragon. Lifestyle has a positive effect on purchasing decisions at the executive clothing store in Paragon. The results of the coefficient of determination of the results of analysis of multiple linear calculations can be seen that the number of adjustments R2 obtained is 0,63,2 or 63,2%. This shows that brand image, product positioning, and lifestyle have an influence on purchasing decisions in the executive store at the paragon mall solo.